The reality of interest in Arab children’s literature: a descriptive analytical study (Al-Academy, 2024)
The literature presented to the Arab child, including inherited tales and melodies, contributes to the formation of the child's culture and enables him or her to accomplish uniqueness in a world where the cultures and knowledge presented to them today are intertwined. As the child grew up with his family in accordance with a particular pattern of customs, traditions, and legacies, his intellectual and linguistic structure formed. The child of today has not had the opportunity to learn, converse with the elderly, or play while listening to inherited stories and melodies. The child grew up within a system of knowledge and data that contributed to his education and indoctrination. Children's literature contributed to the formation of a generational divide in terms of linguistic dictionaries related to cultures and identity concepts.From this standpoint, the current research aims to investigate the reality of interest in the literature of the Arab child by examining the most important Arab initiatives for recording children's stories and shedding light on some international and Arab models in this field.The research followed descriptive analytical research methods in investigating the most important stories and initiatives for the registration of children's literature globally and in the Arab world, and the research came out with a number of recommendations, the most important of which is the need to intensify attention to Arab children's literature because of its role in shaping children's culture through diversity of shapes, concepts, symbols, and words. In addition to the necessity of building a linguistic dictionary for the Arab child, focus should be placed on Arabic culture and identity.